The Association of Social Connectivity and Body Weight With the Onset of Type 2 Diabetes: Findings From the Population-Based Prospective MONICA/KORA Cohort. Issue 9 (13th November 2022) - Atasoy, Seryan; Johar, Hamimatunnisa; Kruse, Johannes; Lukaschek, Karoline; Peters, Annette; Ladwig, Karl-Heinz
ABSTRACT: Objective: Low levels of social connectivity are related to the onset of type 2 diabetes mellitus (T2D), and this study investigates the role of body weight in this association. Methods: In a sample of 9448 participants followed for a mean of 15.3 years (186, 158.5 person-years) from the Monitoring of Trends and Determinants in Cardiovascular Disease Augsburg/Cooperative Health Research in the Region of Augsburg population-based cohort conducted in Germany, we investigated the association of social connectivity, measured by the Social Network Index, and body mass index (BMI) with the risk of clinically validated T2D incidence using stratified Cox proportional hazards regression models adjusted for sociodemographic, life-style, cardiometabolic, and psychosocial risk factors. Results: During a mean follow-up of 14.1 years (186, 158.5 person-years), 975 (10.3%) participants developed T2D. Participants with low social connectivity developed T2D at a higher rate than socially connected participants (10.0 versus 8.0 cases/10, 000 person-years); however, BMI played a significant role in the association of social connectivity with T2D ( p < .001). In comparison to their socially connected counterparts, low social connectivity was associated with a higher rate of T2D incidence in normal-weight (6.0 versus 2.0 cases/10, 000 person-years), but not overweight (13.0 versus 13.0 cases/10, 000 person-years) or obese participants (32.0 versus 30.0 cases/10, 000 person-years). Correspondingly, Cox regression analysis showed that 5-unit increments in BMI increased the risk of T2D in socially connected participants (hazard ratio = 3.03, 95% confidence interval = 2.48–3.79, p < .001) at a substantially higher rate than in low socially connected participants (hazard ratio = 1.77, 95% confidence interval = 1.45–2.16, p < .001). Conclusion: The detrimental link between low social connectivity and increased risk of T2D is substantially stronger in participants with a lower BMI.